Student Satisfaction Index of Merdeka Belajar Kampus Merdeka (MBKM) at Tanjungpura University - Harahap, Reiki Nauli (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is one of the educational policy innovations. As a program, MBKM is designed to achieve certain goals, including matching students' abilities with the market (industry) and the beneficiary (student) 's satisfaction with the program. This study aims to measure the index of student satisfaction with implementing MBKM. The measurement process uses an evaluation study framework by the Kementerian Pendayagunaan Aparatur regarding excellent service. This research used a descriptive quantitative analysis approach, interviewing 349 respondents from all faculties at Tanjungpura University. This number was obtained from the final result of the number of indicators multiplied by five, then multiplied by the number of faculties. There are nine variables (indicators) measured in this study. The study's results stated that the average value of the student satisfaction index was 3,923, with a percentage of 78,458. This value is included in the